PENGEMBANGAN PURWARUPA SISTEM PEMANTAU BANJIR LAHAR DINGIN MEMANFAATKAN PENGUKURAN INTENSITAS GETARAN DAN KEDALAMAN ALIRAN BERBASIS JARINGAN SENSOR NIRKABEL IQRF - , Agung Priyanto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
s Volcanic mudflows or lahars commonly occur following volcanic eruptions. Lahar can cause catastrophic destruction in their paths because of their energy and speed. Huge volume of lahars can bury dwelt areas. Lahars have consistency, viscosity and approximate density of wet concrete, thus they make higher vibration intensity on the riverbanks when flowing down compared to what water does at the same depth and channel. These different vibration intensities when combined with the depths of flow can become a useful indication of lahar events. Additional front-end sensors were built in this study